Patient pathway analysis of tuberculosis diagnostic delay: a multicentre retrospective cohort study in China. (July 2021) - Zhang, Lu; Weng, Tao-Ping; Wang, Hong-Yu; Sun, Feng; Liu, Yuan-Yuan; Lin, Ke; Zhou, Zhe; Chen, Yuan-Yuan; Li, Yong-Guo; Chen, Ji-Wang; Han, Li-Jun; Liu, Hui-Mei; et al.
Abstract: Objectives: Delay in diagnosis of tuberculosis (TB) is an important but under-appreciated problem. Our study aimed to analyse the patient pathway and possible risk factors of long diagnostic delay (LDD). Methods: We enrolled 400 new bacteriologically diagnosed patients with pulmonary TB from 20 hospitals across China. LDD was defined as an interval between the initial care visit and the confirmation of diagnosis exceeding 14 days. Its potential risk factors were investigated by multivariate logistic regression and multilevel logistic regression. Hospitals in China were classified by increasing size, from level 0 to level 3. TB laboratory equipment in hospitals was also evaluated. Results: The median diagnostic delay was 20 days (IQR: 7–72 days), and 229 of 400 patients (57.3%, 95%CI 52.4–62.1) had LDD; 15% of participants were diagnosed at the initial care visit. Compared to level 0 facilities, choosing level 2 (OR 0.27, 95%CI 0.12–0.62, p 0.002) and level 3 facilities (OR 0.34, 95%CI 0.14–0.84, p 0.019) for the initial care visit was independently associated with shorter LDD. Equipping with smear, culture, and Xpert at initial care visit simultaneously also helped to avoid LDD (OR 0.28, 95%CI 0.09–0.82, p 0.020). The multilevel logistic regression yielded similar results. Availability of smear, culture, and Xpert was lower in level 0–1 facilities than in level 2–3 facilities (p < 0.001, respectively). Conclusions: Most patients failed to be diagnosed at the initial care visit. Patients who went to low-level facilities initially had a higher risk of LDD. Improvement of TB laboratory equipment, especially at low-level facilities, is urgently needed. Graphical abstract: Image 1